Density of Fe‐Ni‐C Liquids at High Pressures and Implications for Liquid Cores of Earth and the Moon. Issue 3 (3rd March 2021) - Zhu, Feng; Lai, Xiaojing; Wang, Jianwei; Amulele, George; Kono, Yoshio; Shen, Guoyin; Jing, Zhicheng; Manghnani, Murli H.; Williams, Quentin; Chen, Bin
Abstract: The presence of light elements in the metallic cores of the Earth, the Moon, and other rocky planetary bodies has been widely proposed. Carbon is among the top candidates in light of its high cosmic abundance, siderophile nature, and ubiquity in iron meteorites. It is, however, still controversial whether carbon‐rich core compositional models can account for the seismic velocity observations within the Earth and lunar cores. Here, we report the density and elasticity of Fe90 Ni10 ‐3 wt.% C and Fe90 Ni10 ‐5 wt.% C liquid alloys using synchrotron‐based X‐ray absorption experiments and first‐principles molecular dynamics simulations. Our results show that alloying of 3 wt.% and 5 wt.% C lowers the density of Fe90 Ni10 liquid by ∼2.9–3.1% at 2 GPa, and ∼3.4–3.6% at 9 GPa. More intriguingly, our experiments and simulations both demonstrate that the bulk moduli of the Fe‐Ni‐C liquids are similar to or slightly higher than those of Fe‐Ni liquids. Thus, the calculated compressional velocities ( v p ) of Fe‐Ni‐C liquids are higher than that of pure Fe‐Ni alloy, promoting carbon as a possible candidate to explain the elevated v p in the Earth's outer core. However, the values and slopes of both density and v p of the studied two Fe‐Ni‐C liquids do not match the outer core seismic models, suggesting that carbon may not be the sole principal light element in Earth's outer core. The high v p of Fe‐Ni‐C liquids does not match the presumptive v p of the lunar outer core well, indicating that carbon is less likely to be its dominant light element. Plain Language Summary: Light elements such as H, C, O, Si, P, and S are considered to be present in the predominantly Fe‐Ni liquid cores of the Earth and the Moon. Determining whether a light element is a principal candidate in the core relies chiefly on measuring or calculating the density and sound velocity of the liquid alloys of Fe‐Ni and the light element and comparing with results from seismological studies. The controversies in previous studies on the sound velocity of Fe‐Ni‐C liquids have resulted in debates on whether carbon can be the major light element in Earth's or lunar core. In the present study, we combined experiments and theoretical calculations to investigate the density and elasticity of Fe‐Ni‐C liquids at high pressures. The results show that alloying of carbon lowers the density while increasing the incompressiblity and the sound velocity of Fe‐Ni liquids. Compared with the seismological results on the Earth's core, carbon can be a major light element in Earth's liquid core especially if it co‐exists with other light elements that lower both the density and sound velocity. Based on current models of the lunar core, carbon is less likely to be the dominant light element in the lunar liquid core. Key Points: High‐pressure density and elasticity of Fe90 Ni10 ‐3 wt.% C and Fe90 Ni10 ‐5 wt.% C liquids were determined by experiments and computations Compared to liquid Fe, Fe‐Ni‐C liquids were found to be less compressible and thus possess higher v p at high pressures Carbon can be among the major light elements in Earth's outer core; but is less likely to be the dominant light element in lunar liquid core